Design Technologies in Promoting the Advertisement for National Product: وسام عبد الامير كريم المالكي (Al-Academy, 2021)
The current research is concerned with studying the variables in the promotion process which influence the advertisement design structure, as the accomplished design and construction process is subject to many variables, whether they were intellectual or technological, internal or external variables. These variables may overlap in order to get a comprehensive system for the artistic configuration, that any design in its content reaches the highest levels of perfection is connected to the extent of its compliance with and approximation to these variables, that is why we find their reflections deeply rooted in the individual's mind, especially the designer artist who is influenced by everything surrounding him forming knowledge systems responsive and harmonious with these variables, thus reflected on his cognition and consequently his performance so he affects and gets affected by the rest of the design modes. That was a motivation for the researcher to address the research problem and conduct the current study through the following question: what is the role of the design technologies in promoting the advertisement for the national product?The researcher, in the theoretical framework, reviewed in the first section: the concept of design technology. In the second: promotion and marketing advertising. The third: typographic elements in advertisement design. The analysis unit, in the research procedures, has been determined. That is represented by considering every advertisement an analytical unit as it carries an integrated communication idea that ideas can be derived from through the analysis. Thus, in the analysis process the researcher not only aims at extracting the ideas conveyed by the advertisements (the samples) but also to get benefit through revealing the variables and the extent of their influence in the design structure.